Menakar Ulang Batas Usia Perkawinan: Edukasi Hukum atas Dispensasi Kawin dan Implikasinya dalam Pencegahan Stunting di Kalangan Pelajar - Nurrahman Fajrul Sinrang; Firman Husain (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Early marriage remains an issue with negative impacts on the health and quality of the younger generation, particularly through the risk of stunting in children. This article discusses the results of a counseling session titled "Marriage is Not Just Legal: Legal Education on Marriage Dispensation and Its Implications for Preventing Stunting Among Students" conducted at SMA Negeri 3 Parepare. The counseling aimed to raise students' awareness about the relationship between the marriage age limit, marriage dispensation, and the health impact on children, specifically the risk of stunting. The methods used include deconstruction, brainstorming, material delivery, reconstruction, and evaluation through pre-tests and post-tests. The results show a significant improvement in students' understanding from both medical and legal perspectives. The discussion focuses on analyzing the contradictions in legal norms regarding the marriage age limit and marriage dispensation, which often cause implementation issues. This counseling emphasizes the importance of integrating legal education and reproductive health as a preventive strategy to reduce early marriage and prevent stunting. Thus, this program contributes to shaping a healthy, legally aware younger generation capable of making mature and responsible marriage decisions.